How much of Raymond Vernon's product cycle thesis is still relevant today: evidence from the integrated circuits industry - Rasiah, Rajah; Yap, Xiao Shan (Inderscience, 2019)
Vernon's product cycle thesis has increasingly been questioned as industries experienced differentiation and dispersal of production stages, while the need for proximity for interactions to take place between scientists and engineers, and consumers ended following the introduction of computerised inventory and production, and planning systems. This paper re-examines this thesis using the integrated circuits (IC) industry. The results show that IC multi-nationals have continued to retain frontier R&D and wafer fabrication activities at locations endowed with strong human capital and research centers. However, IC firms are attracted to relocate frontier R&D activities in distant host-sites, such as USA, Japan, Spain, Germany, Russia and Israel that are endowed with sophisticated science, technology and innovation infrastructure, and scientists and engineers. Also, IC manufacturing is too knowledge-intensive to be attracted to the least developed countries. Copyright © 2019 Inderscience Enterprises Ltd.